MAPPING OF FLOOD RISK ZONES IN KAFANCHAN TOWN, JEMA’A LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Ayuba, Comfort Gwasmen; Ajobunu, Saliu Ibrahim; Umar, Jibril Haruna (FUDMA JOURNAL OF SCIENCES, 2024)
Floods are defined as water disasters that causes temporal or permanent consequences in an environment. This research focused on the Mapping of Flood Risk Zones in Kafanchan town, Jema’a local government area by the utilization of field survey and GIS in other to identify and map out the flood prone areas in kafanchan. Multicriteria Method was used for evaluation of the flood risk areas by using various criteria like rainfall data, distance to road, drainage density, and slope. Findings revealed that heavy rainfall, inadequate drainage and slope are the major causes of flooding. From the findings the flood risk map identified places with high, moderate and low vulnerability. Results showed that flood disasters have detrimental effect on people and property. The flood tragedy significantly harmed the environment as well as socio-economic sector. In the research area, the threat of flood disaster has not been addressed by Disaster management/response organizations. Findings, however, showed that these initiatives are insufficient to reduce the threat and risk of flooding in the research area. This study helps government and policymakers in zoning to avoid future flood events from causing tremendous havoc in the study area and providing Early Warning Systems for the area.